1996
DOI: 10.1111/j.1600-051x.1996.tb00502.x
|View full text |Cite
|
Sign up to set email alerts
|

Increased release of free oxygen radicals from peripheral neutrophils in adult periodontitis after Feγ‐receptor stimulation

Abstract: The release of free oxygen radicals and degranulation was studied in neutrophils from 14 patients with adult periodontitis and 14 age- and sex-matched healthy controls. The neutrophils were activated by Fc gamma-receptor stimulation, using Staphylococcus aureus opsonized with gamma globulin. Release of oxygen radicals was measured as luminol-enhanced chemiluminescence. Degranulation was assessed as release of elastase, measured with a specific substrate and as release of lactoferrin measured with ELISA. The ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
109
0
4

Year Published

1996
1996
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 126 publications
(115 citation statements)
references
References 38 publications
2
109
0
4
Order By: Relevance
“…Although IFN-␥ has previously been shown to "prime" for neutrophil ROS generation in a stimulusdependant manner (46), we now demonstrate that type I IFN can perform a similar function. Taken together, these data indicate that increased peripheral blood type I IFN levels in periodontitis patients have the potential to serve as a priming factor and could contribute to the reported neutrophil hyperresponsivity with respect to Fc␥R-mediated ROS generation (7)(8)(9)(10).…”
Section: Discussionmentioning
confidence: 70%
See 3 more Smart Citations
“…Although IFN-␥ has previously been shown to "prime" for neutrophil ROS generation in a stimulusdependant manner (46), we now demonstrate that type I IFN can perform a similar function. Taken together, these data indicate that increased peripheral blood type I IFN levels in periodontitis patients have the potential to serve as a priming factor and could contribute to the reported neutrophil hyperresponsivity with respect to Fc␥R-mediated ROS generation (7)(8)(9)(10).…”
Section: Discussionmentioning
confidence: 70%
“…By using microarrays not tailored for the disease we were able to elucidate transcriptional changes that were previously not part of current understanding. These studies have identified several functional groups of genes up-regulated in periodontitis patients' neutrophils compared with healthy controls, providing a better understanding of the molecular processes underpinning this highly prevalent disease in which peripheral neutrophils generate increased levels of ROS in the presence and absence of stimulation (7)(8)(9)(10).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has also been reported that peripheral polymorphonuclear leukocytes from periodontitis patients show more than two-fold higher chemiluminescence following Fcg receptor stimulation than healthy control polymorphonuclear leukocyte (14). This polymorphonuclear leukocyte hyperreactivity may be due to these cells moving in the circulation through periodontal lesions or may be a constitutive feature of pa-tients with periodontal disease.…”
Section: Hyper-reactive Mononuclear Phagocytesmentioning
confidence: 95%